FETOMATERNAL OUTCOME IN DIFFERENT MODES OF DELIVERY IN PATIENTS WITH ECLAMPSIA - Abrar, Saida (Journal of Postgraduate Medical Institute, 2022)
Objective: To evaluate the fetomaternal outcomes of different modes of delivery in pregnancies complicated by eclampsia at and after 24 weeks. Methodology: We conducted a prospective observational study of 352 women, aged 14-47 years, with eclampsia at >24 weeks of gestation at the Department of Obstetrics & Gynaecology, Women and Children Hospital Bannu, Pakistan from April 2017 to Dec 2018. The primary outcome measures were maternal mortality and maternal near-miss. The secondary outcome measures were perinatal morbidity and mortality. Results: There were 172 women in the vaginal delivery (VD) and 180 in the cesarean delivery (CD) group. The mean age was 31.46 ±10.17 years (range 14-47 years). Most of the women were 21-40 years, 179 (50.85%). There were more unbooked and referred cases in the CD group, 171 (95%) versus 150 (87.2%) (p<0.05), and 131 (72.8%) versus 63 (36.6%) (p<0.000) respectively. The VD group had more maternal deaths, (13.40% versus 6.11%, p<0.021), severe maternal outcomes, (47.09% versus 14.44%, p<0.000), and life-threatening complications, (33.72% versus 8.88%, p<0.000); HELLP (5.81% versus 1.66%, p<0.039), DIC (4.65% versus 0.55%, p<0.015), cardiac dysfunction (3.48% versus 0%, p<0.011), and sepsis (4.65% versus 1.11%, p<0.046). The perinatal outcome was also poor in women with a VD, with higher stillbirths (20.93% versus 07.77%, p<0.000), and perinatal deaths (31.39% versus 12.77%, p<0.000). Conclusion: Eclampsia is associated with grave fetomaternal complications. There is an increase in the number of elective CD in women with eclampsia, which is associated with less morbidity and mortality than VD.